TROILITE IN THE CHONDRULES OF TYPE-3 ORDINARY CHONDRITES: IMPLICATIONS FOR CHONDRULE FORMATION - THE NATURE OF THE S- AND NI-BEARING PHASE(S) - Rubin A.E.; Sailer A.L.; Wasson J.T. (My University, 1999)
The presence of primary troilite in chondrules requires that nebular temperatures were <650 k (the 50% condensation temperature of s) at the time chondrule formation and that chondrules were molten for periods short enough ( to avoid significant volatilization s. we examined 226 intact all textural types from eight unshocked weakly shocked ordinary chondrite falls low petrologic type determine origin troilite in chondrules; 68 are ll3.0 semarkona. there is a high probability primary (i.e., was present among precursors) if it completely embedded mafic silicate phenocryst, located within one-half radius apparent center part an opaque assemblage with igneous texture. based on these criteria, 13% semarkona set as whole contain troilite. most remaining probably primary, but does not meet three criteria. occurs next tetrataenite some spherules low-feo semarkona, implying ni required form came can accommodate 5 mg g temperatures>1170 K) but much less Ni at lower temperatures; because this is far higher than the metamorphic temperature inferred for Semarkona (~670 K), the troilite must be primary. Primary troilite fitting the three criteria occurs in a smaller fraction of low-FeO [FeO/(FeO + MgO) in olivine and/or low-Ca pyroxene not greater than 0.075] than high-FeO porphyritic chondrules in Semarkona (9% vs. 33%). Coarse-grained low-FeO porphyritic chondrules appear to contain somewhat more troilite on average than those of medium grain size.We found a few troilite-free, metallic-Fe-Ni-bearing, low-FeO chondrules that contain Na2O-bearing augite and Na2O- and K2O-rich mesostasis; these chondrules were probably formed after ambient nebular temperatures cooled below 910 K (the 50% condensation temperature of Na) and before they reached 650 K. Literature reports of rare fayalitic microchondrules in the rims around a few normal-size chondrules suggest that chondrule formation persisted until nebular temperatures cooled below 500 K.Secondary troilite occurs in a few percent of Semarkona chondrules as thin veins mobilized by shock; troilite or pyrrhotite in the outer portions of some chondrules occur within opaque assemblages containing magnetite, carbide, Ni-rich sulfide, awaruite, and Co-rich kamacite produced by parent-body hydrothermal alteration.